2018
DOI: 10.3389/fphys.2018.01610
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Evidence and Olfactory Reception of a Single Alarm Pheromone Component in Halyomorpha halys

Abstract: Halyomorpha halys is a major herbivore insect in the fruit orchards of China that has become a devastating invasive pest in North America and Europe since its accidental introductions in the 1990s and 2000s, respectively. Like other hemipteran insects, H. halys releases defensive chemicals against natural enemies, including (E)-2-decenal, which is an aldehyde associated with alarm pheromones. In this study, a series of electrophysiological and behavioral tests were conducted to characterize the alarm functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…However, these assumptions remain to be tested. Our findings, together with those of Paula et al (2016) and Zhong et al (2017Zhong et al ( , 2018, would provide a basis to understand the physiological functions of HhalOBPs and may facilitate to develop approaches for behavioral interference of the pest.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, these assumptions remain to be tested. Our findings, together with those of Paula et al (2016) and Zhong et al (2017Zhong et al ( , 2018, would provide a basis to understand the physiological functions of HhalOBPs and may facilitate to develop approaches for behavioral interference of the pest.…”
Section: Discussionmentioning
confidence: 76%
“…We found that HhalOBP8, 16, 25, and 30 were highly expressed in H. halys antennae. Coincidently, these four HhalOBPs had higher binding activities to the major component of the alarm pheromone, ( E )-2-decenal, of H. halys ( Zhong et al, 2018 ). The epoxides (3 S ,6 S ,7 R ,10 S )-10,11-epoxy-1-bisabolen-3-ol and (3 R ,6 S ,7 R ,10 S )-10,11-epoxy-1-bisabolen-3-ol were identified as the main components of the aggregation pheromone of H. halys ( Khrimian et al, 2014 ; Weber et al, 2014 ).…”
Section: Discussionmentioning
confidence: 93%
“…Upon HhTAR1 silencing, H. halys 2 nd instar nymphs were tested in their olfactive performances by an innovative behavioral assay. This assay measured the repellent effect of (E)-2-decenal, one of the main alarm compounds released by H. halys under threats, on 2 nd instar nymphs (Zhong et al, 2017;Zhong et al , 2018;Nixon et al, 2018). The HhTAR1-dsRNA treatment caused a reduced sensitivity to (E)-2-decenal in comparison to the LacZ-dsRNA control nymphs.…”
Section: Discussionmentioning
confidence: 99%
“…The negative control acetone or the positive repellent control (E)-2-decenal were applied to a filter paper (1 cm x 1 cm) that was placed under the green bean. The positive control (E)-2-decenal, dissolved in acetone, was tested at a fixed quantity of 10 µg, a value ensuring the maximum repellence activity against the H. halys nymphs (Zhong et al, 2018). The number of H.…”
Section: Repellence Assaymentioning
confidence: 99%
“…N-Phenyl-1-naphtylamine (1-NPN) was used as the fluorescent probe, and the binding constants of OBP with 1-NPN were determined according to the Scatchard equation. Then, the binding abilities of T. japonicus OBPs and (E)-2-decenal were investigated following the protocol as described by Zhong et al (2018). Each OBP was tested three times and means were used for the analysis.…”
Section: Competitive Fluorescence-binding Assaymentioning
confidence: 99%